Intrinsic defect migration in Be12Ti. (January 2021) - Jackson, M.L.; Burr, P.A.; Grimes, R.W.
Abstract: Be12 Ti is a leading candidate neutron-multiplier material for fusion breeder blankets; yet the evolution of the crystal defects under irradiation is poorly understood. Here, the migration of intrinsic defects in tetragonal Be12 Ti was predicted using atomic scale computer simulation. Transport of titanium and beryllium through the interstitial, interstitialcy and vacancy-mediated models was considered, along with the migration of divacancy clusters, previously identified as important to the defect chemistry of Be12 Ti. It was found that titanium defects exhibit much higher migration energies than beryllium for most migration pathways, leading to a dramatic difference in the self-diffusivity of the two species. Both beryllium vacancy and interstitial diffusion is close to isotropic with vacancy transport exhibiting the highest self-diffusion coefficient. Migration of beryllium di-vacancies is also isotropic with activation energy equal to that of isolated vacancies. The titanium interstitial exhibits significantly lower migration energy than its vacancy (1.00 eV and 6.75 eV respectively), with both mechanisms strongly anisotropic: the activation energy for [001] migration is at least 5 eV lower than other directions. Even the more exotic mixed titanium beryllium vacancy migration exhibits a much higher migration energy than [001] titanium interstitial transport. The framework used for predicting defect transport kinetics, including vacancy-mediated, interstitial and interstitialcy mechanisms, can be applied to any complex-structured intermetallic compound. Highlights: The self-diffusivity of Be and Ti in Be12 Ti is predicted from atomic scale simulations. Radiation-induced Be vacancy clusters diffuse as fast as dilute vacancies. Be diffusion is fast, isotropic and prevalently vacancy-mediated. Ti diffusion exhibits extreme anisotropy, and is mediated by self-interstitials. Showcase a method for predicting diffusion in complex structure intermetallics.